Analysis of Surah Al-Imran 104 in the Context of Social Leadership - Yudo Zulkarnain; Siti Rohimah (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
This analysis delves into Surah Al-Imran:104 from the Quran, exploring its relevance to contemporary social leadership. The verse emphasizes the importance of promoting goodness while discouraging evil, offering valuable insights for modern leadership paradigms. Through a comprehensive examination of the verse within its Quranic context and classical Islamic exegesis, this research highlights the significance of leaders who uphold moral values and virtuous behavior within their communities. By elucidating the implications of the verse for leadership and exploring its contemporary relevance, the study aims to contribute to understanding Islamic leadership principles and their application to societal challenges. The results reveal the guidance provided by Surah Al-Imran:104 in shaping leaders committed to the betterment of society, leading to success and prosperity. In conclusion, the article underscores the unique perspective offered by this Quranic verse, enriching modern leadership theories with ethical dimensions. This study offers a fresh approach to social leadership by drawing upon Quranic wisdom, providing insights into ethical practices that can benefit society as a whole.